Minimally invasive methods of treatment of pulmonary bleeding - Khuda, Marta; Grubnik, Volodymyr; Severgin, Vladyslav; Dubenko, Dmytro (The Ukrainian Scientific Medical Youth Journal, 2023)
pulmonary bleeding is a life-threatening complication of many diseases, pathological con- ditions and respiratory injuries. In connection with the urgency of the problem of the occurrence of pul- monary bleeding, in recent years, new highly effective methods of diagnosis and treatment of this com- plication have been increasingly used in clinical practice. The main principles of treatment of pulmonary bleeding are prevention of asphyxia and immediate stopping of bleeding. The range of treatment tactics is quite wide: from conservative treatment, temporary cessation of pulmonary bleeding for a period suf- ficient to remove patients from a serious condition, diagnosis of the underlying disease and preparationfor radical surgery, to emergency elimination of this complication. To date, there is no consensus on a single universal method of diagnosis and treatment of pulmonary hemorrhage, therefore, in order to improve the effectiveness of diagnosis and further treatment of this complication, a systematic approach is recommended, which involves combining several methods. Endoscopic methods cannot in all cases accurately determine the source of bleeding, so they are recommended to be combined with radiological studies, CT, angiography of bronchial arteries. With massive pulmonary bleeding, more importance is attached to surgical intervention, which includes endovascular catheter embolization of bronchial ar-teries. X-ray endovascular occlusion is a minimally invasive and highly effective method of stopping all types of bleeding from the bronchial artery pool, which can be used even in extremely critical patients. Minimally invasive methods: endoscopic and endovascular are leading in the diagnosis and treatment of respiratory diseases complicated by pulmonary bleeding. They allow not only to establish the very fact of pulmonary bleeding and its likely source, but also to implement the entire set of measures aimed at stopping bleeding. Despite the reliability and demand of minimally invasive methods, the question of using one or another method to stop pulmonary bleeding remains unclear, which requires further study of their effectiveness, reliability, and economic validity.